Professional Ethicsteachers in the World of Education - Safri, Muhammad; Wafi, Fadhlul (International Journal of Students Education, 2023)
Teachers are professional education with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students. One of the things that teachers need to understand to make the learning process effective is that all students are born with an insatiable curiosity and they all have the potential to fulfill their curiosity. For this reason, teachers need to create a conducive learning environment and challenge students' curiosity. The teacher is a factor that influences the success or failure of the learning process, and therefore teachers must master the principles of learning in addition to mastering the material to be taught. In other words, teachers must be able to create the best possible learning conditions. Teachers play a very important role in helping the development of students to realize their life goals optimally. Children's abilities and potential do not develop optimally without the help of teachers. In this case, it is hoped that teachers can pay attention to students individually, because students are unique human beings, as individuals who are different from one individual to another.